미국시장에 대한 한국의 수출증대와 단기무역보험의 연관성 분석 - 김종권(Jong-Kwon Kim), 유광현(Kwang-Hyun Yu) (무역연구, 2020)
Purpose – This paper is related to study the relations between Korea’s export growth and short-term trade insurance acquisition rate relative to the Korean economy. Because Korea has an export-oriented trade structure, the economic ripple effect of the US market on the Korean economy is enormous, and therefore this study is relevant. Design/methodology/approach– This study conducted various analyses, starting with basic statistics such as average statistics and standard deviations. Second, the data was examined through regression analysis, and lastly, the Granger’s Causality test was conducted. Findings– Findings showed that the average increase and decrease of the acquisition performance of short-term trade insurance is 27.73%, and the average of total US export rate increase and decrease is 3.91%. The standard deviation of the short-term trade insurance acquisition rate was 121.51%, and the standard deviation of the total US export rate was 16.52%. In view of current uncertainties in the external economy, the role of short-term trade insurance seems to be important. Secondly, through regression analysis a decrease in interest rate leads to a positive effect by strengthening export competitiveness due to reduced export companies’ costs, and ultimately, this translates to an increase in total exports. Third, the results of the Granger’s Causality test show that the short-term trade insurance acquisition rate and the U.S. export growth rate are mutually influential. Research implications or Originality– In 2020, Korea’s economic situation is foreseen to be characterized by heightened uncertainty due to external economic conditions and dynamism in its various economic variables. The U.S. economy can continue its boom during the year similar to the period before 2019. Accordingly, it is a meaningful attempt to analyze the relationship between Korea’s export growth and the short-term trade insurance acquisition rate as these have a bearing on US exports. In conclusion, this study implies that we should not overlook the importance of short-term trade insurance in terms of the various credit and market risks in Korea’s exports and the implications of such on the overall Korean economy. KCI Citation Count: 0